Echo-Doppler assessment of ventricular filling pressures in adult Fontan patients. (1st June 2019) - Miranda, William R.; Warnes, Carole A.; Connolly, Heidi M.; Taggart, Nathaniel W.; O'Leary, Patrick W.; Oh, Jae K.; Egbe, Alexander C.
Abstract: Background: Diastolic dysfunction is felt to be part of the natural history of patients with prior Fontan operation. Despite that, data on noninvasive assessment of diastolic function and ventricular filling pressures in Fontan patients are limited. Methods: We included 45 adult Fontan patients who underwent right heart catheterization with pulmonary artery wedge pressure (PAWP) measurement and transthoracic echo-Doppler assessment within 7 days. Offline measurement of systemic atrioventricular valve pulsed-wave (PW) and medial/lateral atrioventricular annular tissue Doppler velocities was performed and correlated to PAWP. Results: Median age was 31.4 years (IQR 24.8–37); 51% of patients were females. Median ventricular ejection fraction was 55% (IQR 50.3–57.5) and median PAWP was 10 mm Hg (IQR 8–11). PW Doppler E velocity ( r = 0.64, p ≤ 0.0001), deceleration time ( r = −0.40, p = 0.008), and E/A ratio ( r = 0.33, p = 0.03) correlated with PAWP. Median medial and lateral E/e′ ratios also correlated to PAWP ( r = 0.71, p = 0.002 and r = 0.75, p < 0.0001; respectively). An E velocity >75 cm/s had 88% sensitivity and 86% specificity [97% negative predictive value (NPV); 58% positive predictive value (PPV)], E/A ratio >1.7 had 100% sensitivity and 61% specificity (100% NPV; 26% PPV), and deceleration time <135 ms had 88% sensitivity and 83% specificity (97% NPV; 58% PPV) for predicting PAWP >12 mm Hg. Conclusion: Our data suggest that PW Doppler atrioventricular E velocity, E/A ratio, and deceleration time could be used to identify adult Fontan patients with normal filling pressures. However, PPVs for PAWP >12 mm Hg were poor. Further studies, particularly prospective, simultaneous echo-catheterization correlation, are critically needed. Highlights: AVV PW Doppler may identify normal filling pressures in adult Fontan patients. However, positive predictive values for PAWP >12 mm Hg were modest. AVV E/e′ might be a better tool but further studies are needed.